Application of Design Speed for Urban Road and Street Network - Ziedonis Lazda; Juris Smirnovs (The Baltic Journal of Road and Bridge Engineering)
Building of arterials in densely populated urban areas needs significant financial expenses. In the situation when the available financial resources for street and bridge construction are limited, the most important issue is to evaluate all possible ways to reduce the total road construction costs what is first of all achieved by reducing geometrical parameters of arterials. These parameters are reduced by changing the design speed, while ensuring an adequate level of traffic safety. Therefore there is a need for a review of standards for the street functions and categories of streets in urban areas. An analysis of average momentary speed impact on urban street and road network design, as well as momentary speed impact on traffic conditions has been done. A relationship between design speed and momentary speed at different capacity ratio of traffic flow has been found.